Faktor Penyebab Penyakit Hipertensi di Klinik BALAD Kota Pariaman dengan Menggunakan Analisis Faktor - Retno Zuliani Okta; Helma Helma (UNIVERSITAS NEGERI PADANG, 2018)
Abstract - This study discusses about the factors of causing hypertensive by using factor analysis methods in Clinic BALAD of Pariaman City. BALAD Clinic of Pariaman city cares for hypertension patients which always increases every year from 2015 until 2017. This study aims to determine the factors that cause hypertension at the BALAD Clinic including age, heredity, exercise, smoking, food and drink, and psychological. This type of research is applied research using primary data. The population in this study all patients who suffer from hypertension August 2017 - April 2018 in Clinical BALAD many as 170 people. Sampling with accidental sampling means that samples taken by chance encountered in the clinic BALAD. Based on the results of research known that the factors of causing hypertension in Clinic BALAD is a factor built by food and psychological variables and factors built by variables of descent and smoking.